Parental resources and child well-being in East Asia: An overview. (April 2020) - Raymo, James M; Dong, Hao
The papers in this special issue use newly available panel data and data from the Program for International Student Assessment (PISA) to examine linkages between parental resources and children's outcomes in China, Japan, and Korea. Specific foci of the papers include regional differences, non-monetary resources, shadow education, gender differences, and the proximity of grandparents. Results demonstrate that, as in western societies, parental education and income are positively associated with child well-being and development in East Asia, but distinctive contextual features contribute to variation in these relationships. It is also clear from the findings that relationships between parental resources and child outcomes are more complicated than suggested by simple emphases on economic inequality and the relative success of children from rich and poor families. Together, these papers contribute a much needed geographic extension to the large cross-national literature on parental resources and children's well-being. The findings provide a valuable empirical basis for assessing the role of context and understanding similarities and differences within East Asia and between the East and West.